Designing Payroll Accounting Information Systems to Enhance Internal Control in Hotels in Sentani, Jayapura, Papua - Galuh Budi Astuti; Nawirah; Liahmad; Ignasius Narew; Telaumbanu, Erikson Adrianus (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study critically examines the role of payroll accounting information systems as a pivotal internal control mechanism within the hospitality industry. Employing a qualitative case study methodology, the research integrates both primary and secondary data sources collected through comprehensive fieldwork, including semi-structured interviews and rigorous document analysis. The investigation uncovers systemic inefficiencies, including the absence of a dedicated finance department, incomplete payroll documentation, and overlapping responsibilities between accounting and payroll staff, collectively undermining payroll accuracy and employee trust. Findings reveal that these structural deficiencies heighten the risk of errors and reduce operational transparency. The study advocates for strategic organizational reforms, including the establishment of an autonomous finance department, clear segregation of payroll and accounting functions, and the implementation of comprehensive payroll documentation—such as detailed employee bank account records, payroll summaries, pay slips, and cash disbursement vouchers. These interventions are projected to substantially enhance the reliability and effectiveness of internal controls in payroll management, thereby mitigating financial risks and fostering greater employee confidence. This research contributes to the broader discourse on leveraging integrated accounting information systems to strengthen internal control frameworks and optimize operational performance in service-sector organizations. The insights offer valuable implications for practitioners and researchers seeking to strengthen internal governance by enhancing technological and procedural aspects of accounting information systems.